Synthesis and Evaluation of Ibuprofen Conjugate with Salicylamide and its Mannich Bases for Analgesic and Antiinflammatory Activities - K. Nair, Deepa; Mishra, Ashutosh; Vijay Kanth, M.S. (Asian Journal of Chemistry, 2016)
Ibuprofen conjugate with salicylamide and its Mannich bases were synthesized and characterized using melting point, TLC, elemental analysis, IR spectroscopy, NMR and mass spectroscopy. Further, the compounds were screened for pharmacological activity which indicated that some Mannich bases of mutual prodrug of ibuprofen and salicylamide were better than their individual parent compound and its mutual prodrug for its analgesic and antiinflammatory activities. They also had lesser ulcerogenic index, an indication of lesser toxicity.